Predictive Factors for Autoimmune Pancreatitis Relapse After 3 Years of Maintenance Therapy. Issue 10 (November 2018) - Nakamura, Akira; Ozawa, Makiko; Watanabe, Takayuki; Ito, Tetsuya; Muraki, Takashi; Hamano, Hideaki; Koinuma, Masayoshi; Kawa, Shigeyuki
Abstract : Objectives: Oral corticosteroid treatment is the standard therapy for autoimmune pancreatitis (AIP) and is highly effective. However, relapse may occur during maintenance therapy (MT). We aimed to clarify the predictive factors for relapse after 3 years of MT for use in deciding on the continuation of long-term MT. Methods: Among 56 retrospectively recruited AIP patients who received corticosteroid remission induction therapy followed by MT for a minimum of 5 years, 38 subjects were enrolled after exclusion criteria and divided into the relapse group of patients who experienced relapse after 3 years of MT and the nonrelapse group of patients who did not. Results: According to multivariate analysis, at least 4 other organ involvement numbers at diagnosis (hazard ratio, 5.82; 95% confidence interval, 1.203–28.192) and IgG of 1400 mg/dL or greater at 3 years of MT (hazard ratio, 4.41; 95% confidence interval, 1.096–17.790) were predictive factors for relapse after MT for 3 years, with patients exhibiting both predictive factors having a higher cumulative relapse rate than those with 1 or fewer predictive factor. Conclusions: We uncovered 2 predictive factors for AIP relapse after 3 years of MT. These findings will assist in deciding corticosteroid therapy regimens at 3 years of MT to minimize AIP relapse risk and adverse corticosteroid effects.